2003
DOI: 10.1034/j.1600-0633.2003.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐related changes in habitat selection by larval grayling (Thymallus thymallus L.)

Abstract: – In a medium‐sized river in northern Finland, larval grayling shifted with growth from shallow habitats with slow velocities, fine substrata and abundant vegetation cover to deeper sites with swifter velocities, coarse substrata and sparse vegetation cover within 3 weeks. Small (17–21 mm) larvae preferred water depths 10–30 cm, substrata dominated by mud or sand (<2 mm), 10–70% vegetation cover and water velocities <10 cm · s−1. Middle‐sized (22–25 mm) larvae preferred 30–90 cm depths, sandy substrata, <40% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
(116 reference statements)
1
30
2
Order By: Relevance
“…Although many studies have shown that microhabitat associations across localised scales are important to fish (e.g. Angermeier, 1987;Aadland, 1993;Jowett & Richardson, 1995;Vadas & Orth, 2001;Nykanen & Huusko, 2003), approaches that perform observations at these small scales alone are unable to detect the association between fish assemblages and large-scale environmental factors. Environmental factors occurring over large spatial scales are of particular importance in large dryland rivers such as the Barwon-Darling, where fish are capable of migrating hundreds of kilometres within their lifetime (Reynolds, 1983;Mallen-Cooper, 1989).…”
Section: Resultsmentioning
confidence: 98%
“…Although many studies have shown that microhabitat associations across localised scales are important to fish (e.g. Angermeier, 1987;Aadland, 1993;Jowett & Richardson, 1995;Vadas & Orth, 2001;Nykanen & Huusko, 2003), approaches that perform observations at these small scales alone are unable to detect the association between fish assemblages and large-scale environmental factors. Environmental factors occurring over large spatial scales are of particular importance in large dryland rivers such as the Barwon-Darling, where fish are capable of migrating hundreds of kilometres within their lifetime (Reynolds, 1983;Mallen-Cooper, 1989).…”
Section: Resultsmentioning
confidence: 98%
“…Availability of suitable habitat is important to potential prey animals, and is a limiting factor in their distribution (Pringle 1982;Hacker and Steneck 1990;Moksnes et al 1998;Phelan et al 2001;Nykänen and Huusko 2003;Kley and Maier 2005). Much research has focussed on the relationship between environmental heterogeneity and species richness and co-existence in un-invaded ecosystems (see Kadmon and Allouche 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It could be possible to cope with these two errors by enhancing the transferability of habitat models or by using multi-objective optimization algorithms. Improving transferability enables a habitat model to represent habitat use of a target species that can change according to sites (Leftwich et al 1997;Mäki-Petäy et al 2002;Guay et al 2003;Huusko 2003, 2004;Vanreusel et al 2007), seasons , life stages (Nykänen and Huusko 2003) and other ecophysiological conditions. This may also contribute to a better understanding of target species or ecosystems which can be obtained from reliable habitat models.…”
Section: Discussionmentioning
confidence: 99%